(untitled) - Ristvet, Lauren (New York, 2007)
This engaging and accessible volume draws on the most recent historical archeological scholarship to tell the stories of human evolution, "gathering and hunting" societies, and the distinct breakthroughs that led to the emergence of the earliest cities, states, and civilizations. Highlighting both the separate paths and the intersecting journeys of diverse human communities, In the Beginning provides the essential but often neglected foundation on which all subsequent historical development was constructed.
Keywords: Human evolution,Civilization, Ancient,Prehistoric peoples